2021
DOI: 10.1111/add.15428
|View full text |Cite
|
Sign up to set email alerts
|

Support can increase use of the AUDIT‐C in Australian Aboriginal Community Controlled Health Services: a cluster randomized trial

Abstract: Background and Aims Unhealthy alcohol consumption is a key concern for Aboriginal and Torres Strait Islander ('Indigenous') communities. It is important to identify and treat at-risk drinkers, to prevent harms to physical or social wellbeing. We aimed to test whether training and support for Aboriginal Community Controlled Health Service (ACCHS) staff would increase rates of alcohol screening and brief intervention. Design Cluster randomized trial. Setting Australia. Cases/Intervention/Measurements Twenty-two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 50 publications
2
22
1
Order By: Relevance
“…Consistent with the results during 12-month active phase [9] Previous studies have shown that multiple organizational levels need to be involved to optimize health service improvement efforts [7,26,27]. Furthermore, the ACCHS' work to sustainably improve Aboriginal and Torres Strait Islander health must be supported by both state and federal government.…”
Section: Discussionsupporting
confidence: 73%
“…Consistent with the results during 12-month active phase [9] Previous studies have shown that multiple organizational levels need to be involved to optimize health service improvement efforts [7,26,27]. Furthermore, the ACCHS' work to sustainably improve Aboriginal and Torres Strait Islander health must be supported by both state and federal government.…”
Section: Discussionsupporting
confidence: 73%
“…This may be explained by the convenience nature of our sample, whereby regular patients, with more opportunities for healthcare providers to assess and document their risk status, were possibly more likely to be approached to participate. 24 with many ACCHS clients presenting to primary care with comorbidities and competing health priorities.…”
Section: Discussionmentioning
confidence: 99%
“…While the RCT improved screening rates, it did not increase the odds of clients receiving brief intervention. 24 Such findings highlight the fact that while screening and documentation of risk factors can act as a prompt for healthcare providers, it does not ensure that preventive care is delivered. Thus, additional strategies will also be needed to help healthcare providers to 'Assess, Advise, Assist, and Arrange support' for those patients identified as at-risk.…”
Section: Implications For Public Health Practicementioning
confidence: 99%
“…Training included: harms related to alcohol; current evidence for screening; culturally secure and accurate administration and interpretation of AUDIT-C; use of annual AUDIT-C screening; responding to a positive AUDIT-C screen; and using service-wide screening data to monitor improvements in screening Implementation approaches incorporated cultural protocols of Aboriginal and Torres Strait peoples such as gender appropriateness, kinship systems and cultural obligations Face-to-face workshops were delivered by an addiction medicine specialist and an Aboriginal health professional (e.g., drug and alcohol worker or other) 4 Data feedback report, based on the bi-monthly data provided by services Graphic representation of proportion of clients screened; proportion drinking at risky levels as measured by AUDIT-C; as well as overall rate of screening over 2-month periods and the last 12-months; and recorded treatment provided Presented as a pdf file with graphics and emailed to service champions and key contacts 5 Bi-monthly teleconference for service champions to exchange improvement ideas and experiences 6 Support to modify practice software to facilitate screening such as inclusion of AUDIT-C in the Adult Health Check, and other electronic forms used for periodic and opportunistic health checks, e.g., over 50 s, pregnancy, pre-consult examination 7 A website with a repository of electronic tools and resources, including screening resources and standard drinks charts, and a private chat platform for champions 8 Financial support for purchase of agreed resources e.g., standard drink cups, clinical handbooks, prevention materials a This table emphasises the screening-specific content of the support model. Fuller description, including elements supporting alcohol treatment, has been published elsewhere [ 12 , 15 ] …”
Section: Methodsmentioning
confidence: 99%